Analisis Pemanfaatan Konten Interactive Multimedia Based Learning Terhadap Peningkatan Kompetensi Belajar Mandiri Mahasiswa Di Masa Pandemi Covid-19 - Anggun Nugroho; Joko Santoso; I Wayan Karang Utama; Shofwan Hanief (LPPM Universitas Putera Batam, 2022)
In the lecture process, a lecturer has the task of delivering several learning concepts, each of which has different characteristics in a very limited time. Often lecturers can only complete lecture material but have not been able to provide more challenges for students to prove and practice their understanding of lecture material. This is very much needed, especially in practical lecture materials that require sufficient understanding and lots of case study exercises. In general, it was found that student learning achievement fell on the implementation of full online learning policies during the CoViD-19 pandemic, this is certainly related to independent learning competence (KBM) which is an important factor in online learning. If this continues to happen, it is feared that it will affect student achievement in the long term. So it takes a sense of care and creativity of lecturers to maintain learning achievement and independent learning competence of students. In this study, an analysis of the relationship and influence between the use of interactive multimedia based learning on student teaching and learning was carried out. The research was conducted in several teaching classes at ITB STIKOM Bali which were divided into experimental class and control class. In the experimental class, the implementation of interactive multimedia based learning content was treated, while in the control class there was no such treatment